The prevalence and associated factors of clinical and subclinical rheumatic heart disease among rheumatic heart disease children admitted in HUSM - Zainol, Ahmad Rodzi (2015)
INTRODUCTION Rheumatic heart disease or rheumatic carditis remains the leading cause of acquired heart disease in children worldwide and continues to be an important public health problem in developing countries. To date, there is no local data regarding the clinical and subclinical rheumatic heart disease. OBJECTIVES: The main objectives of this study is to determine the prevalence of clinical and subclinical rheumatic heart disease and to study the factors associated with both clinical and subclinical rheumatic heart disease in children presented to Hospital Universiti Sains Malaysia. METHODS: This study was conducted via retrospective record review of children with rheumatic heart disease who was referred or admitted to Hospital Universiti Sains Malaysia from 2002 to 2014 who meet all the study criteria. RESULT There were 171 newly diagnosed rheumatic heart disease patients included in this study. The prevalence of clinical rheumatic heart disease and subclinical rheumatic heart disease were 86.5% and 13.5% respectively. The mean age at diagnosis of rheumatic heart disease was 10.8 years old and predominantly male with ratio of 1.1 to 1. The mean age for subclinical rheumatic heart disease was 9 years old and predominantly female. All patients of rheumatic heart disease involved in this study were Malay. Majority of the patients of rheumatic heart disease were from rural areas and it accounted for 60.2%. Patient with rheumatic heart disease mainly have siblings more than 5 which is 52.6%, as compared to number of siblings less or equal to 5 which comprised only 47.4%. The low household income group showed high prevalence of rheumatic heart disease, in which 78.7% of the cases of clinical rheumatic heart disease and comprised of 56.3% cases of subclinical. The majority of the parents were educated up to secondary school level, which was comprised of 76.4%. Age was the only significant factor which influenced subclinical RHD compare to clinical RHD. CONCLUSION The prevalence of subclinical rheumatic heart disease in this study was comparable to other studies. Increasing age was less likely to develop subclinical rheumatic heart disease compare to clinical RHD.